Combination of European system for cardiac operative risk evaluation (EuroSCORE) and Cardiac Surgery Score (CASUS) to improve outcome prediction in cardiac surgery - Dörr, Fabian Alexander; Heldwein, Matthias B.; Bayer, Ole; Sabashnikov, Anton; Weymann, Alexander; Dohmen, Pascal M.; Wahlers, Thorsten; Hekmat, Khosro (Medical science monitor. Basic research, 2015)
Background: We hypothesized that the combination of a preoperative and a postoperative scoring system would improve the accuracy of mortality prediction and therefore combined the preoperative ‘additive EuroSCORE‘ (European system for cardiac operative risk evaluation) with the postoperative ‘additive CASUS’ (Cardiac Surgery Score) to form the ‘modified CASUS’. - Material and methods: We included all consecutive adult patients after cardiac surgery during January 2007 and December 2010 in our prospective study. Our single-centre study was conducted in a German general referral university hospital. The original additive and the ‘modified CASUS’ were tested using calibration and discrimination statistics. We compared the area under the curve (AUC) of the receiver characteristic curves (ROC) by DeLong’s method and calculated overall correct classification (OCC) values. - Results: The mean age among the total of 5207 patients was 67.2±10.9 years. Whilst the ICU mortality was 5.9% we observed a mean length of ICU stay of 4.6±7.0 days. Both models demonstrated excellent discriminatory power (mean AUC of ‘modified CASUS’: ≥0.929; ‘additive CASUS’: ≥0.920), with no significant differences according to DeLong. Neither model showed a significant p-value (<0.05) in calibration. We detected the best OCC during the 2nd day (modified: 96.5%; original: 96.6%). - Conclusions: Our ‘additive’ and ‘modified’ CASUS are reasonable overall predictors. We could not detect any improvement in the accuracy of mortality prediction in cardiac surgery by combining a preoperative and a postoperative scoring system. A separate calculation of the two individual elements is therefore recommended.
Gesehen am 02.06.2020